2018
DOI: 10.1002/jsfa.9387
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive, simple and rapid colorimetric detection of malachite green in water, salmon and canned tuna samples based on gold nanoparticles

Abstract: BACKGROUND Malachite green is used in aquaculture and fisheries as a fungicide and antiseptic and it is also used in industry as a dye. However, malachite green is carcinogenic and highly toxic for humans and animals. In this study, a spectrophotometric method was developed to detect malachite green. The method was based on the surface plasmon resonance property of gold nanoparticles and interaction between malachite green and gold nanoparticles. RESULTS Malachite green–gold nanoparticles were rapidly aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Significantly (p < 0.05) downregulated CYP1A mRNA expression was noticed, which is in conformity to biochemical results of other xenobiotic metabolizing enzyme (XME) enzymes (GST) of the present study. The depressed CYP1A expression can be related to toxicant mediated inhibition of the gene activity [12]. Later, Dhamgaye et al [62] have reported MG as a substrate for CYP1A and credited the xenobiotic metabolism of MG into Leuco-MG (LMG) [63,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly (p < 0.05) downregulated CYP1A mRNA expression was noticed, which is in conformity to biochemical results of other xenobiotic metabolizing enzyme (XME) enzymes (GST) of the present study. The depressed CYP1A expression can be related to toxicant mediated inhibition of the gene activity [12]. Later, Dhamgaye et al [62] have reported MG as a substrate for CYP1A and credited the xenobiotic metabolism of MG into Leuco-MG (LMG) [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…The unrestricted release of dye effluents in water poses non-targeted toxicity to the fish and aquatic organisms, affecting their vision, physiology, genetic constitution, and histology [6][7][8][9]. Despite its reported toxicity, it is still being used illegally in many Asian countries (India and Bangladesh) as an aquaculture therapeutant in Saprolegniasis and Ichthyophthirius multifiliis infection [10][11][12][13][14]. MG has been reported to severely affect the aquatic biota due to its non-biodegradable nature and tendency to bio accumulate [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…While certain reagents can enhance sensitivity and specificity for detection, they often lead to a more complex and costly detection process. For instance, gold nanoparticles can be used to detect color changes via UV-vis spectroscopy, associated with alterations in surface plasmon resonance properties as they aggregate in the presence of specific fungicides in canned tuna [ 49 ]. Similarly, metal-organic frameworks with high affinity to Hg can be employed to detect toxic Hg 2+ ions in canned tuna fish [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Herein, a fast and sensitive detection of TMS in three types of matrices (aquaculture water, fish and shrimp) was realised by the developed TS-DTL system, the TMS LOD (11.0–61.4 ng/mL) was over 16 times lower than the TMS residue limit of the USA (1 μg/mL). There have been various detection methods for MG, as shown in Table 1 , and the LODs of MG have varied from 0.31 to 339.37 ng/mL based on different determination strategies [ 16 , 29 , 30 , 31 , 32 , 33 ]. The quantitative sensitivity of MG by the TS-DTL method was better than that of the ICTS based on orange carbon dots [ 16 ] and fluorescence method [ 30 ], but inferior to the ELISA [ 31 ] and colorimetry methods [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been various detection methods for MG, as shown in Table 1 , and the LODs of MG have varied from 0.31 to 339.37 ng/mL based on different determination strategies [ 16 , 29 , 30 , 31 , 32 , 33 ]. The quantitative sensitivity of MG by the TS-DTL method was better than that of the ICTS based on orange carbon dots [ 16 ] and fluorescence method [ 30 ], but inferior to the ELISA [ 31 ] and colorimetry methods [ 32 ]. Overall, the TS-DTL system developed in this study could not only realise the simultaneous detection of TMS and MG but also be applicable to fish, shrimp matrices and related aquaculture water.…”
Section: Resultsmentioning
confidence: 99%